The association between psychosocial interventions and fertility treatment outcome: A systematic review and meta-analysis. (April 2021) - Katyal, Nitasha; Poulsen, Cecilie Müller; Knudsen, Ulla Breth; Frederiksen, Yoon
Abstract: Objective: Does psychosocial intervention affect pregnancy outcomes in women and couples undergoing assisted reproductive technology (ART) treatment?. Design: A systematic review and meta-analysis of Randomized Controlled Trials (RCTs) evaluating the efficacy of psychosocial intervention on pregnancy outcomes in women and couples undergoing ART treatment. The primary outcome was Pregnancy Rates. Secondary outcomes were Live Birth Rate (LBR) and Abortion Rate (AR). Materials and methods: Databases searched were Pubmed, PsycINFO, Embase, CINAHL and The Cochrane Library. 1439 records were screened, 15 were eligible and included in the meta-analyses ( N = 2434). Data was extracted using the Covidence software. Effect sizes were reported as relative risks with 95% confidence-intervals and p-values. Results: A positive association was found between psychosocial intervention and pregnancy rates (RR = 1.12 CI=(1.01;1.24), p = 0.033). Long-duration interventions and mind-body intervention types were found to be associated with increased pregnancy rates (RR 1.21, CI= (1.04;1.43), p = 0.017) and (RR = 1.25, CI= (1.00;1.55), p = 0.046) respectively. Q and I 2 tests suggested no to low heterogeneity. Funnel plots, Trim and Fill analyses and Fail-safe numbers were applied to adjust for possible publication bias. Conclusions: Our findings suggest a positive association between psychosocial interventions, particularly long-duration interventions, and pregnancy rate in infertile women and couples in ART treatment. The findings are in line with findings from other reviews and meta-analyses exploring the same topic. More good quality RCTs need to be performed to increase the quality of guidance for infertile women and couples. The effect of psychosocial interventions on LBR and AR remain to be examined.